2007
DOI: 10.1074/jbc.m609617200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Promoter Element Containing Multiple Overlapping Xenobiotic and Hypoxia Response Elements Mediates Induction of Cytochrome P4502S1 by Both Dioxin and Hypoxia

Abstract: Cytochrome P4502S1 (CYP2S1) is expressed at high levels in epithelial tissues and is inducible by 2,3,7,8-tetrachlorodibenzo-p-dioxin (dioxin) via the aryl hydrocarbon receptor (AHR). Transcriptional initiation of mouse Cyp2s1 was found to occur at three regions, ϳ198, 102, and 22 nucleotides from the translational initiation codon. Approximately 400 nucleotides upstream of its translational initiation codon, mouse Cyp2s1 contains three overlapping xenobiotic-responsive element (XRE) sequences, which make a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 34 publications
(37 reference statements)
2
40
0
6
Order By: Relevance
“…Although CYP2S1 is similarly expressed (Saarikoski et al, 2005), several previous studies have failed to detect CYP2S1 activity toward a variety of xenobiotics, including cigarette smoke (Wang et al, 2005) or known P450 substrates including benz[a]pyrene . In contrast, others have shown CYP2S1 to be induced by 2,3,7,8-tetrachlorodibenzo-p-dioxin (dioxin) (Rivera et al, 2007) and other chemical agents such as ␣-naphthalene (Karlgren et al, 2005) and atRA (Smith et al, 2003b), suggesting a role for CYP2S1 in xenobiotic metabolism. A role for CYP2S1 in atRA metabolism is confirmed by our results in HaCaT cells, where atRA induces CYP2S1 mRNA expression at a dose previously shown to induce CYP1B1 (Choudhary et al, 2004) and CYP2S1-mediated atRA metabolism in HaCaT cells is very similar to that observed in a CHO-based cell line coexpressing CYP2S1 and CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Although CYP2S1 is similarly expressed (Saarikoski et al, 2005), several previous studies have failed to detect CYP2S1 activity toward a variety of xenobiotics, including cigarette smoke (Wang et al, 2005) or known P450 substrates including benz[a]pyrene . In contrast, others have shown CYP2S1 to be induced by 2,3,7,8-tetrachlorodibenzo-p-dioxin (dioxin) (Rivera et al, 2007) and other chemical agents such as ␣-naphthalene (Karlgren et al, 2005) and atRA (Smith et al, 2003b), suggesting a role for CYP2S1 in xenobiotic metabolism. A role for CYP2S1 in atRA metabolism is confirmed by our results in HaCaT cells, where atRA induces CYP2S1 mRNA expression at a dose previously shown to induce CYP1B1 (Choudhary et al, 2004) and CYP2S1-mediated atRA metabolism in HaCaT cells is very similar to that observed in a CHO-based cell line coexpressing CYP2S1 and CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, human CYP2S1 and CYP2W1 isoforms have also been shown to be transcriptionally regulated by AhR (14,27,28). As such, we investigated whether 5F-203 and GW-610 are able to Induction of CYP1A1 mRNA and protein was observed in all cell lines on treatment of cells with 5F-203 and GW-610, including KM12 and HCC2998 CRC cells which are inherently resistant to 5F-203 ( Fig.…”
Section: Expression Of Cyp1a1 Cyp2s1 and Cyp2w1 In Breast And Crc Cmentioning
confidence: 99%
“…GATCCGGCTCTTGTCACGCAACTCC GAGCTCA GATCTGAGCTCGGAGTTGCGTG AGAAGAGCCG (Denison et al, 1988;Fukuda et al, 2004) Cyp1B1 ACAGCTCCGCACGCAAGGGGGA GGCGACAGGAATTCAGATCTCC CGGGT CTGTCGCCTCCCCCTTGCGTGC GGAGCTGTGAATTCAGATCTCC CGGGT (Eltom et al, 1999) Cyp2S1 CACATGCACGCACGCACGCACA CCAAGGAATTCAGATCTCCCGG GT CTTGGTGTGCGTGCGTGCGTGC ATGTGGAATTCAGATCTCCCGG GT (Rivera et al, 2007) Cyp2S5 CAAAGCCCCTGCTCACTCACGC ACTCTGGAAGCCTGCGAATTCA GATCTCCCGGGT GCAGGCTTCCAGAGTGCGTGAG TGAGCAGGGGCTTTGGAATTCA GATCTCCCGGGT (Arpiainen et al, 2005) Cyp19A1 CGGGAGATCTGAATTCTGAGAG TGAACTGCAGGAAG CGGGAGATCTGAATTCACCTCAT GGCTAAGGCAATG (Baba et al, 2005) a Lengths (bp) of amplified PCR products are indicated. b Dioxin-response elements (DREs) are underlined.…”
Section: Cyp1a1mentioning
confidence: 99%
“…Nuclear extract prepared from Hepa-1c1c7 cells stimulated with TCDD was used as the material containing activated AhR for DNA binding. First to be used were FITC-labeled probes designed for the promoter region of well-characterized AhR target genes, including Cyp1A1, Cyp1B1, Cyp2S1, Cyp2A5, and Cyp19A1 (Arpiainen et al, 2005;Baba et al, 2005;Denison et al, 1988;Eltom et al, 1999;Rivera et al, 2007). These probes gave AhR-binding scores ranging from 2.2 to 3.2 ( Fig.…”
Section: Screening Of Ahr-binding Chip Fragmentsmentioning
confidence: 99%
See 1 more Smart Citation